Cryptococcal endophthalmitis in a patient with malignancy: A case report and literature review - Kamonchanok Phaopraphat; Rujipas Sirijatuphat (Medical Mycology Case Reports)
Cryptococcal endophthalmitis is a rare manifestation of cryptococcal infection, typically occurring in immunocompromised patients. In this case report, we present a 50-year-old female with advanced-stage lung cancer with multiple metastases presenting with blurred vision for 10 days. A diagnostic pars plana vitrectomy revealed Cryptococcus neoformans in the vitreous. She was treated with systemic amphotericin B and flucytosine, followed by fluconazole for consolidation and maintenance, along with intravitreal amphotericin B and voriconazole injections. Her visual acuity improved from counting fingers at 2 feet to 3/60, with a pinhole correction of 6/18 after 10 months of treatment.